Self -affirmation and its relation of tendency toward perfection and the awareness of creativity among fine arts institutions students (Journal Of Educational and Psychological Researches, 2017)
The study aimed to identify self –affirmation degree, tendency degree toward perfection, awareness degree of creativity among fine arts institutions students, and the significant correlation between self -affirmation and its tendency toward perfection, and the awareness of creativity among fine arts institutions students. To achieve these objectives, the author had constructed two scales: one to measure self –affirmation among the sample based on “Lang& Jakobowski theory” (Lang& Jakobowski, 1973) that consisted of (54) item divided into two parts: qualitative and situational. The other scale is to measure the tendency toward perfection depend on (flett & Hewitt, 1991) that composed of (46) item divided into two sections: self-standards and community- standards. Total of (400) male and female fine arts students from three universities: Baghdad, Basra, and Mosul were selected as a sample for this study. The results showed that there was a significant correlation between self -affirmation and its tendency toward perfection and the awareness of creativity, Self –affirmation was medium among chosen sample, and less than medium according tendency toward perfection and the awareness of creativity.